WORKSHOP METODE PENELITIAN TUGAS AKHIR MAHASISWA BIDANG TEKNOLOGI FARMASI DI MASA PANDEMI COVID 19 UNTUK MENGHASILKAN KUALITAS PENELITIAN YANG BAIK - Pitarisa, Agustina Putri; Febrianto, Yahya; Dida, Nurista; Setiyaningsih, Wahyu (LPPM Institut Pendidikan Nusantara Global, 2022)
The spread of Covid-19 has had many impacts in various sectors, one of which is the education sector. Currently, many activities in educational institutions are limited or even stopped. SStudents’final research is also affected since students’ target and desire to obtain maximum results were hindered by Covid-19 which limited them to using laboratories and libraries. The objective of this research is to help students complete their final assignments effectively and to improve the quality of their final project research during the pandemic. It employed the lecture and Q&A methods. Evaluation was carried out by conducting needs analysis and then reporting the results of the data analysis. The results obtained include: 1) final year students already have knowledge related to the equalization of perception of scientific paper and technique of writing scientific paper in pharmaceutical technology, 2) students know the target of completing the cientific paper.